Effect of shape imperfection on the buckling of large-scale thin-walled ellipsoidal head in steel nuclear containment. (March 2018) - Zheng, J.; Li, K.; Liu, S.; Ge, H.; Zhang, Z.; Gu, C.; Qian, H.; Hua, Z.
Abstract: Buckling is a failure mode of a large-scale thin-walled ellipsoidal head for a cylindrical steel containment vessel, which is widely used in nuclear power plants such as AP1000 and CAP1400. Manufacturing processes always induce shape imperfections in large-scale thin-walled ellipsoidal heads. However, the study on the effect of shape imperfections on the buckling of a large-scale thin-walled ellipsoidal head subjected to internal pressure is still lacking. In this work, we first used a 3D laser scanner to measure the overall shape of the ellipsoidal head which has a diameter of 5000 mm, a radius-to-height ratio of 2.0 and a thickness of 5.5 mm. On the basis of the measured overall shape, shape imperfections were determined, and an equation was proposed to quantitatively characterize bulging of weld in the knuckle. Secondly, the measured overall shape and the equation were used to develop FEA models with shape imperfections. Buckling pressures were predicted by using nonlinear FEA. Good agreement between the predictions of the FEA models with shape imperfections indicates that bulging of weld has a considerable effect on buckling pressure. Thirdly, a buckling experiment was performed on the ellipsoidal head and buckling behavior was obtained. The experimental results show that all the buckles occurred at the bulgings of welds. The agreement between the experimental results and the predictions based on the models with shape imperfections is good. At last, FEA models, including different bulging heights of welds characterized by the equation, were established to perform an imperfection sensitivity analysis. Thin-walled ellipsoidal heads subjected to internal pressure demonstrate a significant sensitivity to the bulging height of weld in the knuckle. Highlights: The evolution of the overall shape for a large-scale ellipsoidal head during buckling test was measured by a 3D laser scanner. Finite element models of the ellipsoidal head with shape imperfections were developed. Ellipsoidal heads demonstrate a considerable sensitivity to peaking height of weld.